Ouvidoria geral como unidade de report na Universidade Federal do Ceará - Santos, Juliana Silva dos (2023)
The research examines the Ombudsman of UFC as a supportive unit for university management, aligned with the Public Management Reform of 1995/98, focusing on accountability and governance. The exploratory, documental, and qualitative methodology involved analyzing the Ombudsman’s reports and reviewing literature on public governance, NPM, and the role of Ombudsmen in Higher Education Institutions (HEIs). Institutional documents and the CGU’s "Painel Resolveu" were used, providing a detailed view of institutional practices. The goal is to evaluate how Ombudsmen at HEIs can contribute to strategic decision-making in university administration. Results highlight that Ombudsmen have great potential to add value to strategic management. At UFC, the Ombudsman stood out for its agility, innovation, and transparency in its processes. There is an opportunity to further integrate report data into discussions with top management, enhancing the Ombudsman as a strategic partner in decision-making. The research emphasizes the potential to develop practical resources to guide Ombudsmen in acting more strategically, enhancing their contribution to university governance.